FINANCIAL STATEMENT INTEGRITY : WHAT ARE THINGS THAT INFLUENCE IT? - Safitri, Anisa Zelvia; Andriani, Wiwik; Herman, Lisa Amelia (Jurnal Ilmiah Raflesia Akuntansi, 2023)
This study aims to determine the effect of company size, institutional ownership, profitability and audit quality on the integrity of mining companies' financial statements on the Indonesia Stock Exchange for the 2017-2021 period. The approach used in this study is quantitative. The population is the mining sector companies listed on the Indonesia Stock Exchange for 2017-2021. The sampling technique used was the purposive sampling method, and the data analysis in this study used multiple linear regression analysis. The findings of this study indicate that the variables of firm size, institutional ownership, and audit quality empirically have a positive effect on the integrity of the financial statements of mining sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period, while profitability does not have a significant effect on the integrity of the financial statements of mining companies listed on the Indonesian Stock Exchange listed on the Indonesia Stock Exchange for the period 2017-2021.